An Oral History of the Special Olympics in China Volume 1 Overview - Alford, William P.; Liao, Mei; Cui, Fengming (Economy and Social Inclusion, 2020)
This open access book is unique in presenting the first oral history of individuals with an intellectual disability and their families in China. In this summary volume and the two accompanying volumes that follow, individuals with an intellectual disability tell their life stories, while their family members, teachers, classmates, and co-workers describe their professional, academic, and family relationships. Besides interview transcripts, each volume provides observations and records in real time the daily experiences of people with an intellectual disability. Drawing on the methodologies of sociology and oral history, the summary volume provides an unprecedented account of how people with intellectual disabilities in China understand themselves while also examining pertinent issues of public policy and civil society that have ramifications beyond the field of disability itself.